Microglial M2 Polarization Mediated the Neuroprotective Effect of Morroniside in Transient MCAO-Induced Mice - Liu, Hao; Ou, Mei-Xian; Han, Qiao-Qiao (Frontiers in Pharmacology, 2021)
Morroniside, a secoiridoid glycoside from Cornus officinalis, is a class of small molecule non-peptide glucagon-like peptide-1 receptor (GLP-1R) agonists and possess lots of important biomedical functions. Our previous studies reported that GLP-1R agonist exenatide promoted M2 polarization and the expression of cell-specific anti-inflammatory factor IL-10 in neuropathological pain model. In this study, we proved that morroniside not only induced M2 polarization and stimulated IL-10 expression specifically in cortical primary microglia by p38β MAPK pathway, but also protected nerve cells against H2O2-induced cell oxidative damage and prohibited ischemic injury by reducing infarct size, which at least in part mediated by enhanced expression of microglial IL-10 in the cortical penumbra area in MCAO mice. In general, our results indicated that GLP-1R agonist morronisde might play neuroprotective effect by inducing M2 polarization, and cAMP/PKA/p38β pathway might mediate morroniside-induced expression of IL-10 protein in M2 microglia.